Study on the Relative Degree Improvement of Soil Structure under Different Grasses - Nambiar, K. K. M.; Dayal, Rajbans; Mishra, P. R. (Indian Forester, 1968)
A quantitative evaluation of soil structure in terms of mean-weight-diameter of the aggregates has been done under Cenchrus ciliaris, Dichanthium annulatum and Aristide hystrix in comparison to that under over-grazeda area. The m-W-ds of the aggregate distribution obtained at 0-15 cm; 15-80 Cm; 30-45 cm; and 45-60 Cm depths under Cenchrus ciliaris are 1.400 mm; 0.550 mm 0.880 and 0.264 mm; respectively, and under Dichanthium annulatum, 1.407 mm; 0.504 mm; 0.252mm; and 0.870 mm. The m-w-ds of the aggregate distribution in the surface layers of Cenchrus ciliaris and Dichanthium annulatum are mare than five times the m-w-d of the aggregate distribution in the surface layer of the over-grazed area. The m-W-d of the aggregate distribution under the annual Aristida hystrix thrice that in the case of over-grazed area. The extent of soil aggregation in the surface and sub-surface soils remains to be the same the under over-grazed area. Studies further revealed that the diameter, spread, and vertical extent of the roots play a major role in soil aggregation in deeper layers of the profile.